PERKAWINAN DINI DAN PERCERAIAN: Studi Kasus Perempuan Samin di Kudus Jawa Tengah - Moh Rosyid (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This paper is a qualitative research based on observation and interview among Samin community in Kudus. The purpose of this study is presenting unregistered marriage among Samin community. Samin community is the descendants and followers of Ki Samin Surosentiko, renowned for his nonconformity against the Dutch since 1840s. Following the teaching, Samin people do not registered their marriage and thus they do not feel necessary to obey the government regulation on the minimum age of marriage. The marriage among Samin community will be performed once a girl and a boy perceived to be ready. There are three stages of maturity: adam timur, adam brahi and wong sikep kukuh wali adam. This understanding may lead to child marriage and among its negative impact is divorce. The consequences of unregistered marriage go further to dispute of marital property, right of guardianship, and even conflict between relatives. Nowadays, some Samin people try to find a way to register their marriage in order to get a marriage certificate from the Office of Civil Administration of Kudus. The government needs to pay more attention to the phenomena.